Accounting for the gross ecosystem product (GEP) of forests in nature reserves—taking the Taishan Scenic and Historic Spot as an example - Chongqing Xu; Teng Zhao; Yuting Shao; Xiaoxia Li; Guihuan Yan (PLoS ONE, 2025)
How to measure the economic value of forest ecosystems is an important research topic for sustainable development. Existing quantitative systems for ecosystem values were compared and analyzed on the basis of characteristics of forest ecosystems in the Taishan Scenic and Historic Spot with reference to the Technical Guidelines for Accounting for the Gross Value of Ecological Products in Shandong Province. Two new indicators, namely, forest protection and scientific research and education, were added to the accounting system, forming a “forest sample” applicable to the accounting of GEP in nature reserves to better understand the synergistic effect between conservation and development. The forest GEP of the Taishan Scenic and Historic Spot in 2022 and 2023 was calculated according to the index system developed in this work, and the results of these calculations were used to analyze the environmental changes and current status of the Taishan forest ecosystems. The results revealed that the GEP of forest ecological products in Taishan Scenic and Historic Spot in 2023 was 4.478 billion yuan, the value of the unit area was 496,900 yuan per hectare, and the value of the regulating service was 2.312 billion yuan, which was slightly greater than the value of the cultural service, at 2.186 billion yuan. The values of secondary classification of forest ecosystems were determined to be in the following order: evergreen coniferous forests>  deciduous broad-leaved forests>  mixed coniferous and broad-leaved forests>  sparse forests. Compared with that in 2022, the GEP value of forests in Taishan Scenic and Historic Spot has increased by 110%, and ecological protection is more effective.